EVALUATION OF SOCIAL ASSISTANCE RECIPIENT ELIGIBILITY BASED ON INCOME AND NUMBER OF DEPENDENTS USING THE FUZZY MAMDANI APPROACH - Andhini, Avrillia; Amelia, Alin; Antika, Anggi; Harianja, Lexa; Andani, Sundari Retno (PT Siantar Codes Academy Publisher, 2025)
This study aims to evaluate the eligibility of social assistance recipients by considering income and family dependents using the Mamdani fuzzy logic approach. A key issue in the current selection process of social assistance recipients lies in the limitations of binary classification methods, which are rigid and incapable of fully representing the diversity of socioeconomic conditions in society. By applying the Mamdani fuzzy method, this research incorporates linguistic variables such as